Characterization of the Myeloid Cell Populations’ Resident in the Porcine Palatine Tonsil - Soldevila, Ferran; Edwards, Jane C.; Graham, Simon P.; Stevens, Lisa M.; Crudgington, Bentley; Crooke, Helen R.; Werling, Dirk; Steinbach, Falko (Frontiers in Immunology, 2018)
The palatine tonsil is the portal of entry for food and air and is continuously subjected to environmental challenges, including pathogens, which use the tonsil and pharynx as a primary site of replication. In pigs, this includes the viruses causing porcine respiratory and reproductive syndrome, and classical and African swine fever; diseases that have impacted the pig production industry globally. Despite the importance of tonsils in host defense, little is known regarding the phenotype of the myeloid cells resident in the porcine tonsil. Here, we have characterized five myeloid cell populations that align to orthologous populations defined in other mammalian species: a CD4+ plasmacytoid dendritic cell (DC) defined by expression of the conserved markers E2.2 and IRF-7, a conventional dendritic cell (cDC1) population expressing CADM1highCD172alow and high levels of XCR1 able to activate allogeneic CD4 and CD8 T cells; a cDC2 population of CADM1dim cells expressing FLT3, IRF4, and CSF1R with an ability to activate allogeneic CD4 T cells; CD163+ macrophages (Mϴs) defined by high levels of endocytosis and responsiveness to LPS and finally a CD14+ population likely derived from the myelomonocytic lineage, which showed the highest levels of endocytosis, a capacity for activation of CD4+ memory T cells, combined with lower relative expression of FLT3. Increased knowledge regarding the phenotypic and functional properties of myeloid cells resident in porcine tonsil will enable these cells to be targeted for future vaccination strategies to current and emerging porcine viruses.